An Analysis of the Outcomes and Complications of Ultrasound Guided Corticosteroid Injection on Tendinopathy in the Foot and Ankle - Benjamin Jacques MS; Miraj N. Desai MD; Chase Gauthier MD; Tyler Gonzalez MD, MBA; J. Benjamin Jackson MBA. MD (Foot & Ankle Orthopaedics)
Category: Ankle; Other Introduction/Purpose: Corticosteroid injections are commonly used in the clinical setting for the treatment of foot and ankle tendinopathy, although there is limited research into their efficacy and rate of complications. The purpose of this study is to examine the patient-reported outcomes and complications, specifically tendon rupture, associated with ultrasound-guided corticosteroid injections for foot and ankle tendinopathy. Methods: A retrospective review was conducted of patients who underwent corticosteroid injection into the extensor hallucis longus, extensor digitorum longus, flexor digitorum longus, posterior tibial, anterior tibial, peroneal, or Achilles tendons for the treatment of foot and ankle tendinopathy between June 2020 and September 2022. Demographic information, incidence of complications, incidence of surgical intervention, and patient-reported outcomes were recorded. A total of 131 patients were included in the study population, with 73 (55.7%) patients receiving a posterior tibial tendon injection, 53 (40.6%) receiving a peroneal tendon injection, and 6 (4.6%) receiving an injection of a different tendon. The average follow-up was 27.8 weeks (range: 3.4 to 111.3). Continuous and categorical data were expressed as a mean and percentage, respectively. Paired Student’s t-test was utilized to compare pre- and post-procedure patient-reported outcomes. Multivariable analysis was utilized to control for confounding variables. All p< 0.05 were considered statistically significant. Results: There were 2 (1.6%) reported ruptures, both of which involved the peroneal tendon, and 22 (16.8%) patients who required surgical treatment of their affected tendons following their injection. Multivariable analysis demonstrated no specific patient or procedure factors were significantly associated with an increase in the tendon rupture rate. Overall, patients who received a corticosteroid injection had significant improvements in their pain interference (63.3 vs 58.7, p< 0.001), physical function (38.9 vs 41.3, p=0.032), and mobility (37 vs 39.7, p=0.006) scores. There was no significant difference in the amount of improvement between those receiving a posterior tibial tendon and peroneal tendon injection regarding pain interference (4.6 vs 4.9, p=0.805), physical function (3.2 vs 1.9, p=0.294), and mobility (3.4 vs 3.1, p=0.865) scores. Conclusion: There is a lack of efficacy and safety data surrounding corticosteroid injections for use in foot and ankle pathology. This study demonstrates patients receiving a corticosteroid injection for the treatment of foot and ankle tendinopathy had significant improvements in their patient-reported outcomes with a 1.6% tendon rupture rate. These results demonstrate corticosteroid injections are an effective treatment for foot and ankle tendinopathy, but further research is necessary to fully categorize the safety of this procedure.